PREVALENCE OF ORAL MUCOSA DISEASES IN A REGIONAL TEACHING HOSPITAL IN PERÚ, 2014– 2018. - Suarez-Rojas , Yuvicxa Samantha; Romero Gamboa, Julio Cësar; La Serna Solari, Paola Beatriz (Horizonte Sanitario, 2021)
Objective: To determine the prevalence of diseases of the oral mucosa in the dental service of the regional teaching hospital Las Mercedes Chiclayo, 2014–2018.Materials and methods: descriptive, retrospective, cross-sectional study; through simple random sampling 370 clinical records of patients of legal age were reviewed by means of data collection sheet, taking into account the levels of the general population, gender and age.Results: it was found that the prevalence rate is high with 52.7% between 2014 and 2018. The most common diseases were bacterial such as necrotizing periodontitis with 21.0%, and among other diseases occupying the first place is the abscess with 64.1%; within the ages with a higher prevalence they are between 31 and over with 62.9% and with respect to gender, the female obtained 59.0%Conclusions: the prevalence of diseases of the oral mucosa is high, it is higher in the female gender and in ages over 31 years and over in the dentistry service of the las Mercedes Chiclayo Regional Teaching Hospital, 2014-2018.Keywords: Prevalence, disease, oral mucosa.